Analysis of Government Policy on MSME Development and Resilience - Siskawaty Yahya; Fatmah Ma’ruf (Eastasouth Institute, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in improving regional economic growth, creating employment opportunities, and strengthening community economic resilience. However, MSME development in Gorontalo Province still faces various challenges, including limited access to capital, low human resource capacity, taxation complexity, and weak adaptation to digital transformation and economic crises. This study aims to analyze the influence of government policy on MSME development and resilience in Gorontalo Province through five main variables, namely tax policy, financing and access to capital, training and capacity development, crisis response policy, and sectoral/specific policy. This study applies a quantitative approach using explanatory research. Research data were collected by distributing questionnaires to 150 MSME actors in Gorontalo Province using purposive sampling. The data were analyzed using multiple linear regression. The results show that financing and access to capital have a positive and significant effect on MSME development and resilience, with a significance value of 0.003 (<0.05). Training and capacity development also have a positive and significant effect, with a significance value of 0.011 (<0.05). Furthermore, crisis response policy and sectoral/specific policy show significant effects, with significance values of 0.018 and 0.027, respectively. Meanwhile, tax policy has a positive but insignificant effect on MSME development and resilience, with a significance value of 0.086 (>0.05). The coefficient of determination shows an R Square value of 0.709, indicating that the research variables explain 70.9% of MSME development and resilience, while the remaining 29.1% is influenced by factors outside this study. This study concludes that adaptive, inclusive, and integrated government policies are essential for improving the competitiveness and sustainability of MSMEs in Gorontalo Province.